2002
DOI: 10.1007/3-540-46002-0_23
|View full text |Cite
|
Sign up to set email alerts
|

A Temporal Logic Based Theory of Test Coverage and Generation

Abstract: Abstract. This paper presents a theory of test coverage and generation from specifications written in EFSMs. We investigate a family of coverage criteria based on the information of control flow and data flow and characterize them in the branching time temporal logic CTL. We discuss the complexity of minimal cost test generation and describe a method for automatic test generation which employs the capability of model checkers to construct counterexamples. Our approach extends the range of applications of model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 24 publications
0
75
0
Order By: Relevance
“…While checking correctness, the model checker reports counterexample(s) that violate a correctness criterion. While generating test inputs, the model checker generates paths that are witnesses to a testing criterion encoded as a safety property (see, e.g., [30,36]). For a reported counterexample, the model checker also reports the input heap configuration, the path condition for the primitive input fields, and the thread scheduling, which can be used to reproduce the error.…”
Section: Checking Safety Properties and Generating Test Inputsmentioning
confidence: 99%
“…While checking correctness, the model checker reports counterexample(s) that violate a correctness criterion. While generating test inputs, the model checker generates paths that are witnesses to a testing criterion encoded as a safety property (see, e.g., [30,36]). For a reported counterexample, the model checker also reports the input heap configuration, the path condition for the primitive input fields, and the thread scheduling, which can be used to reproduce the error.…”
Section: Checking Safety Properties and Generating Test Inputsmentioning
confidence: 99%
“…Test case generation with regard to coverage of data flow graphs is considered in [33,58]. A flow graph G is defined as a tuple G = (V, v s , v f , A), where V is a finite set of vertices, v s ∈ V is the start vertex, v f ∈ V is the final vertex, and A is a finite set of arcs.…”
Section: Control and Data Flow Coverage Criteriamentioning
confidence: 99%
“…Hong et al [58] assume the existence of a special predicate exit, which is true in any exit state (e.g., in the final vertex of a data flow graph). It is also suggested that the initial state can be used as an exit state, such that test cases can be seamlessly executed.…”
Section: Fault Visibilitymentioning
confidence: 99%
“…Blom et al [12] and Hong et al [13] extend this idea by formalizing standard coverage criteria (all-definitions, all-uses, etc.) using observers (or temporal logic).…”
Section: Comparison To Related Workmentioning
confidence: 99%